Arabic Grammar, Epistemology, and Civilizational Thought: A Philosophical Inquiry into Islamic Heritage - Solehah Yaacob (Tunas Harapan Ummat Foundation, 2025)
This paper examines the philosophical, epistemological, and civilizational dimensions of Arabic grammar and its central role in shaping Islamic intellectual heritage. Moving beyond a purely technical study of syntax and morphology, it situates Arabic linguistic thought within a comprehensive civilizational framework, illustrating how grammar functions as an instrument of knowledge production, critical reasoning, and ethical reflection. Drawing on classical sources such as Sibawayh, al-Farabi, al-Jurjani, and Ibn Jinni, alongside modern scholarship on Orientalism and linguistics, the study highlights the intricate relationship between language, intellect, and revelation. Arabic grammar emerges not merely as a tool for correct speech but as a philosophical discipline reflecting epistemological rigor, logical coherence, and the resilience of Islamic civilization in the face of external critique. The analysis further demonstrates that mastery of grammar facilitates critical thinking, preserves textual integrity, and ensures the continuity of knowledge across generations. Overall, the findings suggest that the study of Arabic grammar is inseparable from the broader pursuit of intellectual, ethical, and cultural understanding within Islam.